PENGGUNAAN MODEL PEMBELAJARAN INTERAKTIF PADA MATERI TUMBUHAN - Astuti, Rini Nafsiati (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2008)
This article tries to discuss about the using of interactive teaching model to help students to understand and develop plant concept in their daily lives. Interactive teaching model is a teaching model that focuses on students’ questions aspect. Interactive teaching model of the plant concept is based on constructivist approach contain characteristic of science teaching. Teaching characteristic of plant concept is by pay attention and consider the students’ early knowledge which can be gained from the environment outside the school. Teacher can help find out the students’ knowledge as early understanding about plant concept and also give the opportunity for students to construct their knowledge. The steps to apply the interactive teaching model are preparation, before views, exploratory activities, students’ question, investigations, after views and reflections. The use of interactive teaching model can help the students to increase their understanding about plant concept and motivate them to interest to study science.Keywords: Interactive teaching, constructivist, concept